Aesthetic and Mechanical Suitability of a Clear Synthetic Resin as a Unconventional Binder for Road Pavements - Marco Pasetto; Andrea Baliello; Giovanni Giacomello; Emiliano Pasquini (Advances in Materials Science and Engineering)
Current environmental awareness interests several aspects of civil engineering, including road construction. Indeed, new challenges related to environmental pollution and landscape preservation must be faced. In this sense, clear road pavement surfaces represent an effective technology aimed at guaranteeing environmental-friendly aesthetic pavements. The use of clear synthetic resin as a binder involves several benefits for the mitigation of in-service reached temperatures and the heat distribution within pavements (with appreciable effects on pavement mechanical performance too). The present paper illustrates an experimental study aimed at analysing the chromatic and mechanical properties of a clear synthetic resin and thus its suitability as a binder for road pavement mixes. Chromatic characteristics were assessed through digital image analysis at different aging conditions. A dynamic shear rheometer was used to evaluate the linear viscoelastic properties as well as fatigue and rutting potential of the binder in a wide range of temperatures and frequencies. A conventional 35/50 penetration grade bitumen was also investigated for comparison purposes. The clear resin exhibited limited changes in colour (darkening effects), mainly in the case of short-term aging. On the other hand, a low temperature-dependency of such a binder was observed up to 58°C. Slightly increased aptitude to rutting at the higher temperatures was detected, even if it is worth noting that clear in-service mixtures would achieve lower temperatures than traditional “black” materials at a given environmental condition (air temperature, solar radiation, etc.). The resin also exhibited a softer behaviour, along with an enhanced fatigue resistance. Overall, the studied innovative binder showed promising results in view of its effective use in road paving.